حصر وتقييم العيون المائية الطبيعية ببلدية البيضاء في الجبل الأخضر - فرج سليمان عبدالرحيم مازق (The Libyan Journal of Science, 2024)
In this study, 22 natural water springs spread on the second edge of the Green Mountain in the municipality of Al-Bayda were counted and evaluated. productivity, use and exploitation. Twenty Samples were collected from these springs in February 2023, and these samples were analyzed in the laboratories of Al Baydah Food Control Center and the laboratories of the Susah desalination plant, the results then comparing with these values of the Libyan standard for drinking water (2015) concerned with the physical characteristics of drinking water, inorganic indicators and inorganic contents Organic and microbial pollution (bacterial), it was found that 5 natural water springs are not suitable for drinking due to their microbial contamination with Coliform bacteria, and 15 natural water springs are suitable for drinking according to the Libyan standard, and 2 of the springs were not sampled for technical and natural reasons.